2011
DOI: 10.1364/oe.19.008693
|View full text |Cite
|
Sign up to set email alerts
|

Strehl ratios characterizing optical elements designed for presbyopia compensation

Abstract: We present results of numerical analysis of the Strehl ratio characteristics for the light sword optical element (LSOE). For comparison there were analyzed other optical imaging elements proposed for compensation of presbyopia such as the bifocal lens, the trifocal lens, the stenopeic contact lens, and elements with extended depth of focus (EDOF), such as the logarithmic and quartic axicons. The simulations were based on a human eye's model being a simplified version of the Gullstrand model. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 59%
“…21 Moreover, computational results demonstrated the uniformity of Strehl's ratio of the LSL, which is almost constant along the entire length of the focal segment. 26 The ability of the LSL to correct presbyopia was studied in a model of the presbyopic human eye illuminated by white light. 22 The results showed that the LSL enables defocus compensation in the range of 0 to 4 D. These properties make the LSL valuable for ophthalmic applications and for presbyopia correction in particular.…”
mentioning
confidence: 99%
“…According to previously reported theoretical studies, numerical simulations, and qualitative experiments [12][13][14][15][16][17][18], an element of this kind can form recognizable images of acceptable quality in the presence of a defocus of 0-4 diopters. The LSL demonstrated its superiority over other solutions designed especially for multifocal and EDF imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This gives rise to one of their important advantages as compared with the remaining elements: namely, the independence of their optical power range with respect to the pupil's diameter [14]. Numerical simulations and experiments have demonstrated interesting characteristics of the LSOEs in terms of their uniformity, high Strehl ratios [15], and the visual Strehl ratio [16] within the assumed range of defocus. Their imaging properties have also been analyzed by means of the modulation transfer function (MTF) [17] and through the calculation of two parameters showing similarity between the object and its image: namely, a root mean square deviation and a correlation coefficient [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several diffractive elements with EDOF imaging properties, of radial (e.g., axicons 13 and axilens 14 ) and angular (e.g., light sword 15 ) modulation, have been recently considered for presbyopia compensation in aged human vision. [16][17][18] In Ref. 19, the authors describe a family of computergenerated DOEs that perform as generalized zone plates capable to focus light into an arbitrary line segment with any orientation with respect to the optical axis.…”
Section: Introductionmentioning
confidence: 99%